SEDIMENTOLOGICAL AND GEOCHEMICAL CHARACTERISTICS OF OUTCROP SEDIMENTS OF SOUTHERN BIDA BASIN, CENTRAL NIGERIA: IMPLICATIONS FOR PROVENANCE, PALEOENVIRONMENT AND TECTONIC HISTORY (2016)
Integrated sedimentological and geochemical studies have been carried out on the sediments of the Lokoja and Patti Formations within the southern Bida Basin with a view to deducing the provenance, palaeodepositional characteristics and tectonic history of the sediments. Field observations show that the Lokoja Formation is made up of conglomerates, coarse to medium grained sandstone and claystone while the Patti Formation consists of medium – fine grained sandstone, claystone, shale, siltstone and ironstone. Pebble morphometry of the Lokoja Formation indicates fluvial environment while granulometric study of the sandstone indicates that they are medium to coarse grained and poorly sorted. Sandstone petrography showed that quartz is generally > 65.98 % while feldspar ranged from 6.45 to 25.97 % and classified the basal Lokoja Sandstone as arkose while the upper sequence and the sandy facies of the Patti Formation are subarkose. Heavy mineral assemblages are mainly; zircon, rutile, tourmaline and staurolite, with ZTR index ranging from 62 to 78%, indicating immature sandstone. The dominant major oxide constituent within the Lokoja Formation are; SiO (55.4 - 64.10%), AlO 2 2 3 (18.65 - 19.66%), FeO (1.76-3.15%) while the composition each of MgO, CaO, NaO and KO is < 4%. On 2 3 2 2 the other hand, sediments of the Patti Formation have higher SiO (56.62-79.26%) and relatively lower values for 2 AlO (13.28 - 19.28%) and FeO (0.84 - 1.65%). The trace elements are dominated by Sr (165.4-411.9ppm) and 2 3 2 3 Ba (635-908ppm) in the Lokoja Formation while Zr (644.9-1969.8 ppm) has higher values in the Patti Formation. In both units, Ce (46.6-235.8 ppm), La (25.8-116.4 ppm), and Nd (18.1-95.9 ppm) are the most abundant rare earth elements with both trace and rare earth elements concentrating more in the finer clastics of the Patti Formation. The ternary plots of framework composition indicated a passive continental block provenance, oxidizing and humid paleoclimatic condition for the sediments. The plots of Th-Sc-Zr/10, Th/Co versus La/Sc and KO/NaO against SiO lie within felsic rocks region. The study concluded that the sediments 2 2 2, were sourced from the adjacent south-western and north-central basement complex of Nigeria and deposited in a fluvial setting.